2021
DOI: 10.32598/irj.19.1.1211.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Self-compassion, Positive and Negative Affect, and Marital Quality in Infertile Women: A Systematic Review and Meta-analysis

Abstract: Objectives: Infertility presents extensive psychological effects on infertile couple’s marital life, especially in women during infertility treatment. Studying the essential psychological factors and their correlations on a large scale could rehabilitate the mental health of infertile women and facilitate the stressful process of infertility treatment. This systematic review aimed to study the literature and relationships among self-compassion, positive and negative affect, and marital quality in infertile wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Hucker et al demonstrated online, mindfulness-based, cognitive-behavioral therapy for female with sexual disorders and relationship functioning had signi cant impact on promotion sexual and emotional intimacy [39]. Infertility and its related treatments had adversely in uenced on self-esteem, self-image, sexual relationship and couple intimacy [40]. Although the challenges caused by infertility have a negative effect on both men and women, women are more affected by this problem than men [41].…”
Section: Discussionmentioning
confidence: 99%
“…Hucker et al demonstrated online, mindfulness-based, cognitive-behavioral therapy for female with sexual disorders and relationship functioning had signi cant impact on promotion sexual and emotional intimacy [39]. Infertility and its related treatments had adversely in uenced on self-esteem, self-image, sexual relationship and couple intimacy [40]. Although the challenges caused by infertility have a negative effect on both men and women, women are more affected by this problem than men [41].…”
Section: Discussionmentioning
confidence: 99%